2021
DOI: 10.1002/pssr.202000538
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Phase‐Change Memory Performance by Means of GeTe/Sb2Te3 Superlattices

Abstract: GeTe/Sb2Te3 superlattices (SLs) obtained by sputtering are integrated in phase‐change memory (PCM) devices with a “wall structure”. The high structural quality of SLs deposited on TiN or SiNx layers, used as metallic bottom heater and dielectric bottom layer in PCM devices, is established by X‐ray diffraction, for as‐grown SLs and after an annealing corresponding to the maximum thermal budget during the integration process. Scanning transmission electron microscopy (STEM) images of SLs within PCM cells confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…Subsequent studies, however, revealed a crystalline-to-amorphous phase-transition behavior in a similar SL structure, indicating the possible controversy in the switching mechanism. Different mechanisms such as enhanced thermal efficiency, [10][11][12][13][14] stacking fault [15] or strain-assisted transition, [16,17] and partial amorphization [18] have also been suggested in more recent works. Still, studies so far lack a detailed analysis of the crystalline state in the set state.Besides, in previous studies, physical growth methods, such as sputtering and molecular beam epitaxy used to grow the SL films, cannot grow conformal film on highly topographical surfaces.…”
mentioning
confidence: 99%
“…Subsequent studies, however, revealed a crystalline-to-amorphous phase-transition behavior in a similar SL structure, indicating the possible controversy in the switching mechanism. Different mechanisms such as enhanced thermal efficiency, [10][11][12][13][14] stacking fault [15] or strain-assisted transition, [16,17] and partial amorphization [18] have also been suggested in more recent works. Still, studies so far lack a detailed analysis of the crystalline state in the set state.Besides, in previous studies, physical growth methods, such as sputtering and molecular beam epitaxy used to grow the SL films, cannot grow conformal film on highly topographical surfaces.…”
mentioning
confidence: 99%
“…[5,6] Note that [(GeTe) 4 nm /C 1 nm ] 10 has similar performance as the so-called "interfacial Phase-Change Memories" (iPCM) in terms of RESET current reduction. [16,17] Thus, ML devices annealed at 425 °C show promising properties in terms of I RESET reduction for the development of high-density PCMs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34–38 ] Conventional thermal‐based transitions were reported in superlattice devices. [ 39,40 ] However, quasi‐2D amorphization in the superlattice is unlikely due to the close melting temperature of GeTe and Sb 2 Te 3 (≈100 °C), which was corroborated by ab initio molecular dynamics simulations. [ 41 ] Partial amorphization was instead achieved in TiTe 2 /Sb 2 Te 3 phase‐change heterostructures, [ 42–45 ] because of the large difference in melting temperature (>500 °C) between the two constituting alloys.…”
Section: Introductionmentioning
confidence: 84%